2009
DOI: 10.2340/00015555-0730
|View full text |Cite
|
Sign up to set email alerts
|

Epidemiology of Chronic Wound Patients and Relation to Serum Levels of Mannan-binding Lectin

Abstract: The aim of this study was to describe the epidemiology of chronic wounds in a large cohort of patients from a tertiary hospital out-patient clinic, and examine the significance of serum mannan-binding lectin for the occurrence and clinical presentation of such wounds. The study comprised 489 consecutive patients with chronic foot and leg ulcers. A clinical classification of wound- aetiology was performed, and mannan-binding lectin was measured in the sera of patients and healthy controls. The patients presente… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
13
0

Year Published

2010
2010
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(13 citation statements)
references
References 26 publications
0
13
0
Order By: Relevance
“…The SUV study is certainly one of the most important epidemiological investigations on vascular ulcers of lower limbs carried out in Italy in the recent years, because of the high quantity of data collected (1163 patients, of whom about 50% followed up until 9 months after start of therapy) and the widespread presence of participating centres (59 centres representing 14 Italian regions). Published epidemiological studies have been performed recently in leg ulcers in Romania (25) and New Zealand (26), in diabetic ulcers in China (27), in hypertensive leg ulcers in France (28) and in chronic leg wounds in Denmark (29); to our knowledge, however, the SUV study is the only one that has involved more than one thousands patients affected by different types of leg ulcers (venous, arterial, diabetic, mixed, etc. ).…”
Section: Discussionmentioning
confidence: 99%
“…The SUV study is certainly one of the most important epidemiological investigations on vascular ulcers of lower limbs carried out in Italy in the recent years, because of the high quantity of data collected (1163 patients, of whom about 50% followed up until 9 months after start of therapy) and the widespread presence of participating centres (59 centres representing 14 Italian regions). Published epidemiological studies have been performed recently in leg ulcers in Romania (25) and New Zealand (26), in diabetic ulcers in China (27), in hypertensive leg ulcers in France (28) and in chronic leg wounds in Denmark (29); to our knowledge, however, the SUV study is the only one that has involved more than one thousands patients affected by different types of leg ulcers (venous, arterial, diabetic, mixed, etc. ).…”
Section: Discussionmentioning
confidence: 99%
“…However, the identification and opsonization of infectious agents are dependent on the binding of the protein lectin with mannose (MBL) [52-54]. Some studies suggest that a deficiency in serum MBL levels in patients with CVUs culminates in the incapacity of complement system activation, facilitating the installation of infections [55,56]. Thus, the differential expression of protein Complement C3 in the lesion microenvironment is the result of the activation of the defense system against infectious agents, and also suggests the installation of the inflammatory process in the region.…”
Section: Discussionmentioning
confidence: 99%
“…We could not establish evidence that MBL deficiency was related to the healing rate of CVLUs in this pilot study. However, a large cohort study by Bitsch et al (16) showed a higher frequency of MBL deficiency among CVLU patients compared with healthy controls, thus suggesting MBL‐supplemented serum therapy as a subject for a controlled clinical trial. This notion is further encouraged by a case report where an MBL‐deficient patient suffering from both chronic leg and surgical wounds experienced improved healing after receiving substitution therapy with plasma‐derived MBL (48).…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, deficiency of MBL has been associated with impairment of the spontaneous and necessary separation of the eschar in a mouse MBL-null burn wound model (15). In a recent study of chronic leg and foot ulcer patients, serum MBL levels were shown to differ between wounds of different aetiologies, with CVLU patients having a significantly higher frequency of MBL deficiency (16).…”
Section: Key Pointsmentioning
confidence: 99%